2008
DOI: 10.1080/10903120802099526
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Stroke Recognition by Emergency Medical Dispatchers andParamedics—San Diego Experience

Abstract: In our EMS system, EMD using MPDS Stroke protocol with a high compliance has a higher sensitivity than paramedics using CSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 19 publications
6
86
3
Order By: Relevance
“…4 However, delays in presentation and specialist assessment frequently prevent patients from receiving rtPA. Emergency medical dispatch sensitivity and positive predictive value (PPV) for identifying stroke is < 50%, [7][8][9] and this is compounded by long delays in patients accessing emergency medical services (EMSs). 10 Studies have shown that activation of the EMSs is the single most important factor in the rapid triage and treatment of acute stroke patients.…”
Section: Fundingmentioning
confidence: 99%
“…4 However, delays in presentation and specialist assessment frequently prevent patients from receiving rtPA. Emergency medical dispatch sensitivity and positive predictive value (PPV) for identifying stroke is < 50%, [7][8][9] and this is compounded by long delays in patients accessing emergency medical services (EMSs). 10 Studies have shown that activation of the EMSs is the single most important factor in the rapid triage and treatment of acute stroke patients.…”
Section: Fundingmentioning
confidence: 99%
“…9,[15][16][17][18][19][20] Most research has demonstrated that MPDS and other EMD systems identify most but not all urgent calls with a considerable degree of overtriage. [7][8][9]11,16,18,[21][22][23] One intriguing study that linked dispatch, prehospital, and emergency department records of over 28,000 patients noted that a small subset of MPDS codes were associated with a greater than 90% predictive ability for ED discharge.…”
Section: Introductionmentioning
confidence: 99%
“…413-422, 2013 Copyright Author's personal copy (6), with the dispatch priority of Delta (D), and the modifier of a known history of asthma (1A). Several studies have examined the predictive accuracy of MPDS and other EMD systems for a variety of outcomes, including paramedic-assigned acuity score, physician diagnosis of an acute illness, cardiac arrest, ''Code 3'' or ''lights and sirens'' return, and the need for Advanced Life Support (ALS) intervention (9,(15)(16)(17)(18)(19)(20). Most research has demonstrated that MPDS and other EMD systems identify most, but not all, urgent calls with a considerable degree of overtriage (7)(8)(9)11,16,18,21,22).…”
mentioning
confidence: 99%